Pengaruh Penerapan Nilai-Nilai Islam Terhadap Kinerja Bank Syariah dengan Menggunakan Maqashid Index: Studi Lintas Negara - Reza, Muhammad; Violita, Evony Silvino (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study aims to examine the effect of the implementation of Islamic values on the performance of Islamic banks.The implementation of the Islamic values is measured by scoring Islamic values disclosure in the annual reports, while the bank performance is proxied by the maqashid index. The sample is taken from Islamic banks from 9 countries with the biggest assets in Islamic banks. The total sample is 26 islamic banks or 79 islamic banks-years observation. The hypotheses are tested using regression of panel data. This study founds that the implementation of Islamic values in Islamic banks positively influences the bank performance. The result of this study demontrates that the implementation of Islamic values in Islamic banks will boost the banks performance.